Hinduism and the ethics of warfare in South Asia: from antiquity to the present - "Roy, Kaushik" (New Delhi, 2012)
This book challenges the view, common among Western scholars, that precolonial India lacked a tradition of military philosophy. It traces the evolution of theories of warfare in India from the dawn of civilization, focusing on the debate between Dharmayuddha (Just War) and Kutayuddha (Unjust War) within Hindu philosophy. This debate centers around four questions: What is war? What justifies it? How should it be waged? And what are its potential repercussions? This body of literature provides evidence of the historical evolution of strategic thought in the Indian subcontinent that has heretofore been neglected by modern historians. Further, it provides a counterpoint to scholarship in political science that engages solely with Western theories in its analysis of independent India's philosophy of warfare. Ultimately, a better understanding of the legacy of ancient India's strategic theorizing will enable more accurate analysis of modern India's military and nuclear policies.
Keywords: Military art and science-India-Philosophy